AUGMENTATION OF FERTILITY IN POSTPARTUM ANESTRUS COWS - TRIPATHY, A K; MOHANTY, D N; DAS, S; MISHRA, P C (The Indian Journal of Animal Reproduction, 2011)
The _main objective of the study was to augment fertility in postpartum anestrus cows by application of Progesterone therapy alone or in combination with Estrogen through parentral (i/m) route. Thirty postpartum anestrus cows allotted to three equal groups were administered intramuscularly progester6ne 500 mg (P- Depot) and estradiol valerate 10 mg (Progynon- depot) on day "0" followed by P-Depot on 7th day (Group I n-10). The Group II (n-1 0)received P-Depot on day "O" followed by Progesterone and estrogen therapy on day 7. But Group Ill (n-10) cows were given only progesterone on corresponding days. Serum P4 concentration was significantly higher (P<0.01) in cows on 7th day post- treatment (5.34±1.7 4 ng/ml) compared to pre-treatment value (1.98±1.09 ng/ml). The estrus response was 100% in Group 11 followed by 90% in Group I cows. The duration of estrus (hrs) was significantly longer in Group II (28.90 ±0.82) compared to Group Ill (21.80±2.00) but not against Group I (25. 77 ± 1. 78). The estrual characteristics (1-4) revealed higher rating values in Group II cows (2. 70±0.32) followed by Group I (2.67±0.37) and Group-Ill (1.80±0.83). The overall conception rates in group I, II and Ill cows 77.78(7), 80.00(8) and 60.00(3) per cent respectively, with significant difference between Group II and Group Ill animals. It is concluded that progesterone and estradiol combination therapy due to their synergistic effect can give higher overall conception rate in postpartum anestrus cows.